Virtual Environment Room as a Didactic Resource for Learning Pathologies Associated with Helicobacter pylori from the Perspective of Medical Students (Research, Society and Development, 2022)
This study composes the master's dissertation entitled virtual environment room as a didactic resource for teaching pathologies associated with Helicobacter pylori, however, it presents a cut in the view of medical students from a Higher Education Institution in the interior of the State of Rio de Janeiro. Participated in this study 116 students who, based on the results of the pre-test, on their previous knowledge about the pathologies associated with H. pylori, participated in a planned and adapted workshop based on the stages of significant learning by David Ausubel adapted by Marco Antônio Moreira. Then, the same initial questionnaire was applied at the post-test moment, to analyze the assimilation from the established interaction, finally, the didactic instrument went through the validation process with the students that was built from the Theory of Elaboration of Psychological Scales from Pasquali. As a result, it was found that the educational product helps to reduce the difficulties linked to the way of understanding and presenting the content on the pathologies associated with H. pylori, offering safety in the medical prescription, with technical perceptions and accuracy.